The Effect of Class Management on Grade Five Students Learning Outcome At State Primary School Number 066654 Kelambir V District Tanjung Gusta Medan Helvetia - Panni Ance Lumbantobing; Ruth Donda Eleonora Panggabean; Maria Friska Nainggolan (BIRCU, 2020)
This study aims to investigate the effect of classroom management on student learning outcomes at class five primary school numbers 066655, distrcit of Kelambir V Tanjung Gusta Medan Helvetia academic year 2019/2020. The analysis technique in this study is a simple regression technique, observing the relationship or effect between variables. The sample of this research is students of class state primary school number 066654 district of Kelambir V Tanjung Gusta Medan Helvetia, which consists of 2 classes, namely class V A totaling 28 students and class V B totaling 28 students. The total number of class V is 56 students. The variable instrument in the study is all valid, while the reliability for all variables is reliable. Based on the results of statistical analysis, it shows that simple linear regression analysis with the regression equation Y = 24.281 + 0.896X forms a linear line and coefficient of regression direction means. The calculation result is obtained Fcount 56.912 in consultation with Ftable for an error rate of 5%, F table = 4.02. Thus Fcount > F table (56.912 > 4.02) for an error level of 5%. Based on the results of the F test calculation, Fcount is 56.912 with sig = 0.000 <0.005 so that Ho is rejected and Ha is accepted, which means there is an effect of class management (X) which is significant towards learning outcomes (Y). This means that the better the classroom management carried out by the teacher, the higher the student learning outcomes.